RELATIONSHIP BETWEEN HOMOCYSTEINE PLASMA LEVELS AND AREA OF MYOCARDIAL INJURY IN ACUTE CORONARY SYNDROMES - Ardhianto P; Endang Purwaningsih; Bachtiar A B (Faculty of Medicine Diponegoro University, 2016)
Background: Increased homocysteine plasma levels are associated with increased thrombosis. Acute coronary syndromes (ACS) is the process of thrombosis in coronary arteries induced by atherosclerosis plaque ruptures, fissures or erosion. The purpose of this study is to analyze the relationship between increased levels of homocysteine in the blood and the area of ischemic injury in myocardium of patients with ACS.Methods: In the frame of Cardio Metabolic Investigation (Carmetin); a cross-sectional study was done among ACS patients (n=40) admitted at Dr. Kariadi Hospital from August to November 2009. Serum homocysteine were obtained by Enzyme Linked Immuno Assay (ELISA) at the arrival. Myocardial injury area were assessed indirectly by levels of cardiac Troponin I (cTnI) at the time of arrival and 24 hours later. Homocysteine levels were divided into quintiles.Results: There were twenty seven male patients (67.5%) and thirteen female patients (32.5%). Eighteen patients (45%) had a negative cTnI (defined as cTnI ≤ 0.10 ng/ml), while twenty two patients had positive cTnI (55%) at arrival. At the peak levels, only one patients had a negative cTnI levels. There is significant relationship between homocysteine level and the peak of cTnI level (p=0.048). Homocysteine levels were significantly higher in cTnI positive than cTnI negative patients (p<0.01).Conclusion: The increased of homocysteine plasma level is associated with increased of myocardial injury area in ACS patients. Keywords: Homocysteine plasma, myocardial injury, acute coronary syndrome